The Asia Pacific Economic Cooperation (APEC): a study in new regionalism, 1989-2009 - Bendebka, Ramzi; Hossain, Ishtiaq (Lambert Academic Publishing, 2012)
The first objective of this study is to determine the main characteristics of new regionalism. The second objective of this book it to apply those characteristics on the Asia Pacific Economic Cooperation (APEC)to determine whether APEC conforms to new regionalism. The study adopts the New Regionalism Theory (NRT) as the framework of analysis. The discussion of NRT is divided into three sections. Firstly, definition of New regionalism. Secondly, the development of NRT from different perspectives. Thirdly, definitions of concepts (the features of new regionalism. The findings of the study can be summarized as follows: the key features of new regionalism are trade liberalization and open regionalism.